DNA damage response in CD133 + stem/progenitor cells from umbilical cord blood: Low level of endogenous foci and high recruitment of 53BP1. (April 2013) - Vasilyev, Stanislav A.; Kubes, Miroslav; Markova, Eva; Belyaev, Igor
Abstract Purpose: Human hematopoietic stem cells (HSC) are thought to be a major target of radiation-induced leukemogenesis and also provide a relevant cellular model for assessing cancer risk. Cluster of designation 133+ (CD133+) is a marker found in human progenitor and hematopoietic stem cells. Our study examined the repair of radiation-induced DNA double-strand breaks (DSB) in CD133 + umbilical cord blood cells (UCBC). Materials and methods: After γ-irradiation, endogenous and induced DSB were evaluated in CD133 + UCBC, CD133 − UCBC and peripheral blood lymphocytes (PBL) in terms of phosphorylated histone 2A family member X (γH2AX) and tumor suppressor p53 binding protein 1 (53BP1) foci. Results: We found that repair signaling in CD133 + UCBC is different from CD133 − UCBC and PBL. These differences include lower endogenous DSB levels and higher 53BP1 recruitment. Conclusions: Our data, together with a recent report on radiation-induced γH2AX and 53BP1 foci in CD34 + cells, indicate enhanced DNA repair capacity in HSC as compared to mature lymphocytes.